Synthesis, Characterization and Photocatalytic Activity of Anatase-Brookite- Rutile Composite TiO2 Nanocrystals Prepared in H2O/Alcohol System - Hu, S.Z.; Li, F.Y.; Fan, Z.P. (Asian Journal of Chemistry, 2011)
Anatase-brookite-rutile composite TiO2 nanocrystals with a narrow particle size distribution and good dispersibility were prepared by a hydrothermal method using TiC14 as the starting material in different H2O/alcohol system. TEM, HRTEM, X-ray diffraction, UV-VIS diffuse reflectance spectra and FT-IR were used to characterize the synthesized particles. The results showed that the presence of alcohol was the key factor which determined the phase content in prepared TiO2. The prepared TiO2 exhibited higher photocatalytic activity than P25 under UV light.